Comparative Perspectives on Work-Life Balance and Gender Equality : Fathers on Leave Alone - O'Brien, Margaret; Wall, Karin (Springer International Publishing : Imprint: Springer, 2017)
This book is open access under a CC BY-NC 2.5 license. This book portrays men's experiences of home alone leave and how it affects their lives and family gender roles in different policy contexts and explores how this unique parental leave design is implemented in these contrasting policy regimes. The book brings together three major theoretical strands: social policy, in particular the literature on comparative leave policy developments; family and gender studies, in particular the analysis of gendered divisions of work and care and recent shifts in parenting and work-family balance; critical studies of men and masculinities, with a specific focus on fathers and fathering in contemporary western societies and life-courses. Drawing on empirical data from in-depth interviews with fathers across eleven countries, the book shows that the experiences and social processes associated with fathers' home alone leave involve a diversity of trends, revealing both innovations and absence of change, including pluralization as well as the constraining influence of policy, gender, and social context. As a theoretical and empirical book it raises important issues on modernization of the life course and the family in contemporary societies. The book will be of particular interest to scholars in comparing western societies and welfare states as well as to scholars seeking to understand changing work-life policies and family life in societies with different social and historical pathways.
Keywords: Social sciences.; Sociology.; Families.; Families -- Social aspects.; Sex (Psychology).; Gender expression.; Gender identity.; elektronické knihy; electronic books